2018
DOI: 10.1097/sla.0000000000002322
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Lymphedema Microsurgery for Breast Cancer-related Lymphedema With or Without Microvascular Breast Reconstruction

Abstract: Microsurgical breast reconstruction did not improve the outcome of BCRL. Improvements in BCRL were better for lymphatic microsurgery than complete decongestive therapy. Moreover, vascularized lymph node flap transfer provided greater improvements in the BCRL than lymphovenous anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
13

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 44 publications
0
82
0
13
Order By: Relevance
“…Furthermore, previous studies suggested that immediate breast reconstruction could reduce the risk of breast cancer‐related lymphedema (BCRL), and the delayed breast reconstruction may release lymphedema symptoms of the lymphedematous arm . However, recently, the senior author's group clearly demonstrated that the outcome of BCRL is not affected by the microsurgical breast reconstruction itself in a study investigating the outcome of lymphatic microsurgery procedures with or without breast reconstruction …”
Section: Vln Flap Donor Site Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, previous studies suggested that immediate breast reconstruction could reduce the risk of breast cancer‐related lymphedema (BCRL), and the delayed breast reconstruction may release lymphedema symptoms of the lymphedematous arm . However, recently, the senior author's group clearly demonstrated that the outcome of BCRL is not affected by the microsurgical breast reconstruction itself in a study investigating the outcome of lymphatic microsurgery procedures with or without breast reconstruction …”
Section: Vln Flap Donor Site Selectionmentioning
confidence: 99%
“…After that, the senior author's group shed some light reporting anatomic studies and clinical application of the groin and submental lymph node flaps transferred to the distal affected extremity . Recent studies have evaluated the positive effects of VLN transfer in the setting of lymphedema and have shown significantly better results for the patients in which the native lymphatic ducts are no longer available when compared to conservative treatments or LVA . A meta‐analysis investigated the outcomes of VLN flaps in comparison to LVA for the treatment of lymphedema .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations